Conditioning With Sevoflurane in Liver Transplantation. Issue 8 (August 2015) - Beck-Schimmer, Beatrice; Bonvini, John M.; Schadde, Erik; Dutkowski, Philipp; Oberkofler, Christian E.; Lesurtel, Mickael; DeOliveira, Michelle L.; Figueira, Estela R. R.; Rocha Filho, Joel A.; Auler, Jose Otavio Costa; D'Albuquerque, Luiz A. C.; Reyntjens, Koen; et al.
<x xml:space="preserve">Abstract</x> Background During times of organ scarcity and extended use of liver grafts, protective strategies in transplantation are gaining importance. We demonstrated in the past that volatile anesthetics such as sevoflurane attenuate ischemia-reperfusion injury during liver resection. In this randomized study, we examined if volatile anesthetics have an effect on acute graft injury and clinical outcomes after liver transplantation. Methods Cadaveric liver transplant recipients were enrolled from January 2009 to September 2012 at 3 University Centers (Zurich/Sao Paulo/Ghent). Recipients were randomly assigned to propofol (control group) or sevoflurane anesthesia. Postoperative peak of aspartate transaminase was defined as primary endpoint, secondary endpoints were early allograft dysfunction, in-hospital complications, intensive care unit, and hospital stay. Results Ninety-eight recipients were randomized to propofol (n = 48) or sevoflurane (n = 50). Median peak aspartate transaminase after transplantation was 925 (interquartile range, 512–3274) in the propofol and 1097 (interquartile range, 540–2633) in the sevoflurane group. In the propofol arm, 11 patients (23%) experienced early allograft dysfunction, 7 (14%) in the sevoflurane one (odds ratio, 0.64 (0.20 to 2.02, P = 0.45). There were 4 mortalities (8.3%) in the propofol and 2 (4.0%) in the sevoflurane group. Overall and major complication rates were not different. An effect on clinical outcomes was observed favoring the sevoflurane group (less severe complications), but without significance. Conclusions This first multicenter trial comparing propofol with sevoflurane anesthesia in liver transplantation shows no difference in biochemical markers of acute organ injury and clinical outcomes between the 2 regimens. Sevoflurane has no significant added beneficial effect on ischemia-reperfusion injury compared to propofol.